2019
DOI: 10.21873/anticanres.13793
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir-Ritonavir Combination Induces Endoplasmic Reticulum Stress and Kills Urological Cancer Cells

Abstract: Background/Aim: Induction of endoplasmic reticulum (ER) stress is a novel approach to cancer treatment. This study investigated the ability of the clinically feasible combination of the human immunodeficiency virus protease inhibitors lopinavir and ritonavir to induce ER stress killing urological cancer cells. Materials and Methods: Renal cancer cells (769-P, 786-O) and bladder cancer cells (UMUC-3, T-24) were used to investigate the ability of the combination to induce ER stress and its mechanism of action. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Protein CYP3A4; ZMPSTE24; CYP3A5; cytochrome P450, family 2, subfamily D, polypeptide 6 (CYP2D6); and caspase 1 (CASP1) are employed an inhibition mode, while CYP3A4 and CYP2C9 predict binding schema (see Figure 3.d.). This pathway prediction is in good agreement with the previous study 61 .…”
Section: Discussionsupporting
confidence: 93%
“…Protein CYP3A4; ZMPSTE24; CYP3A5; cytochrome P450, family 2, subfamily D, polypeptide 6 (CYP2D6); and caspase 1 (CASP1) are employed an inhibition mode, while CYP3A4 and CYP2C9 predict binding schema (see Figure 3.d.). This pathway prediction is in good agreement with the previous study 61 .…”
Section: Discussionsupporting
confidence: 93%
“…ER stress occurs when levels of unfolded proteins exceed from the capacity of ER. This leads to the activation of unfolded protein response (UPR) that, subsequently, stimulates PRKR-like ER kinase (PERK), eukaryotic translation initiation factor 2α (eIF2α), and 78 kDa glucose-regulated protein (GRP78) [ 145 , 146 , 147 , 148 ]. Chrysin administration also impairs ER homeostasis to induce ER-mediated apoptosis in PC cells [ 144 ].…”
Section: Chrysin and Cancermentioning
confidence: 99%
“…Bissinger et al ( 30 ) showed that LPV induced apoptosis in erythrocytes, accompanied by cell shrinkage and phospholipid scrambling ( 30 ). Okubo et al ( 40 ) also showed the anti-proliferative properties of lopinavir/ritonavir (LPV/r) in combination against urological cancer cells. This study used 40/10 μM ratio of LPV/r over 48 h, and indicated that LPV/r treatment induced endoplasmic reticulum (ER) stress and kills urological cancer cells ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Okubo et al ( 40 ) also showed the anti-proliferative properties of lopinavir/ritonavir (LPV/r) in combination against urological cancer cells. This study used 40/10 μM ratio of LPV/r over 48 h, and indicated that LPV/r treatment induced endoplasmic reticulum (ER) stress and kills urological cancer cells ( 40 ). Lopinavir was also shown to inhibit melanoma cell proliferation, induce morphological changes, apoptosis, and reactive oxygen species production, ( 41 ).…”
Section: Discussionmentioning
confidence: 99%